The Effect of Work Stress and Job Satisfaction on Turnover Intention Among Baristas at Coffee Shops in Kuningan - Handika, Rafly Elvana Tri; Alwi, Muhamad (Journal Research of Social Science, Economics, and Management, 2026)
The development of the creative economy sector, particularly the coffee shop industry, has experienced rapid growth and has had an impact on increasing employment, especially for baristas. However, this industry also faces the problem of high employee turnover. This condition indicates the existence of internal factors that influence employees’ intention to leave their jobs (turnover intention), including work stress and job satisfaction. This study aims to analyze the effect of work stress and job satisfaction on turnover intention among coffee shop baristas in Kuningan Regency, both partially and simultaneously. This study uses a quantitative approach with a causal associative research type. The research population consists of all baristas working in coffee shops in Kuningan Regency, with a sample size of 100 respondents using a saturated sampling technique. Data collection was conducted through questionnaires, while data analysis used multiple linear regression with the help of the SPSS version 26 program. The research instruments had undergone validity and reliability tests, as well as classical assumption tests. The results showed that work stress had a positive and significant effect on turnover intention, while job satisfaction had a negative and significant effect on turnover intention. Simultaneously, work stress and job satisfaction have a significant effect on turnover intention. This study is expected to be a consideration for coffee shop managers in improving human resource management to reduce employee turnover rates.